Estudo de toxicidade aguda e subaguda do extrato bruto das cascas de Luehea divaricata Mart. em ratos wistar - Nunes, Letícia Teixeira (2015)
The species Luehea divaricata Martius belongs to the Malvaceae family and is popularly known as "açoita-cavalo." It occurs naturally in northeastern Argentina, eastern Paraguay and northern Uruguay. In Brazil, predominates in the South and Southeast. The stem bark and aerial parts are popularly used for healing wounds in the skin, acne and vaginal washes. This study aimed to identify and quantify phenolic compounds present in the plant and evaluate possible toxicological effects during the acute administration (14 days) and repeated dose 28-day of crude extract of bark in rats. The stems barks were dried, crushed and macerated with 70% ethanol for seven days and shaken daily. The material was filtered and concentrated, thereby yielding the crude extract. The quantification of the phenolic compounds was performed by HPLC and nine phenolic compounds were disclosed the first time in the species, including quercetin (2.69%), rosmarinic acid (1.23%) and vitexin (1.01%). Toxicity studies have been developed as recommended by the Organization for Economic Cooperation and Development (OECD) 423 and 407. In the assessment of acute toxicity, was administered a single dose of 2000 mg / kg in Wistar male and female rats. The animals were followed for 14 days and there was no death or change in behavior. There was a reduction in serum glucose and increased AST in males treated with the extract of the plant. Treated females also increased AST compared to the control group. In addition, there was also significant increase in platelets treated in the two genres. The extract was classified in category 5, according to the OECD 423, with LD50 between 2000-5000 mg / kg. In subacute or acute dose toxicity test repeated male and female rats were divided into four groups: control, 100, 200 and 400 mg / kg. The animals were treated for 28 days and no mortality or changes in behavior. Biochemical, histological and oxidative factors have been changed, especially in the doses of 200 and 400 mg / kg in females. Histological changes indicated mild liver and kidney damage, however slight. The increase in serum glucose may have been the changes in renal function and reduced AST and ALT do not indicate toxicity. The genotoxicity of the extract was evaluated through micronuclei frequency technique and comet assay. The results showed no indications of damage in DNA and attached to other effects corroborate the statement toxicity. The results of this work collaborate in the investigation of pharmacological effects of the plant, as establishing the safe dose range to extract administration.